Hepatite C no Ceará: epidemiologia, morbimortalidade, tratamento e caminhos para eliminação. - Hyppolito, Elodie Bomfim (2024)
Hepatitis C is a serious public health issue. In Ceará, it is estimated that 0.3% of the population is infected. The mortality rate and the effectiveness of hepatitis treatment are unknown. This study evaluated the mortality related to hepatitis C in Brazil spatially and temporally, as well as the effectiveness and impact of Direct Acting Antivirals (DAAs) on hepatitis C mortality in Brazil and Ceará. Methods: This is a two-phase study. The first phase is an ecological study with a spatiotemporal approach that utilized death data in Brazil and Ceará from 2000 to 2020. Death causes related to hepatitis C were identified according to the criteria listed in the Tenth Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10): B17.1- Acute Hepatitis C, B18.2- Chronic Hepatitis C. Mortality data for Brazil and Ceará were obtained from the Mortality Information System (DATASUS, 2021). Population data were obtained from IBGE based on the National Demographic Census (2000 and 2010) and the estimated population for the intercensal years 2003-2009 and 2011-2018 (IBGE, 2022). The second phase consisted of a retrospective and observational study of patients with chronic hepatitis C at reference centers in Ceará (HUWC-UFC, HSJ, and HGF) between October 2015 and December 2023. Inclusion criteria were age over 18 years and PCR-RNA and/or genotyping for hepatitis C. Fibrosis was assessed by liver biopsy and/or elastography and/or APRI and FIB-4. Treatment was defined by the attending physician following Ministry of Health guidelines. Options included sofosbuvir, daclatasvir, simeprevir, ledipasvir, velpatasvir, glecaprevir, pibrentasvir, veruprevir, ombitasvir, dasabuvir, interferon, and ribavirin. Sustained virological response (SVR), considered a cure, was defined as undetectable HCV PCR-RNA 12 weeks or more after treatment completion. Results: Between 2000 and 2020, there were 64,029 deaths due to hepatitis C recorded (SIM), representing 0.26% of deaths in Brazil. High mortality rates were identified in São Paulo, southern Minas Gerais, southern Rio de Janeiro, northern Paraná, southern and coastal Santa Catarina, eastern Mato Grosso do Sul, and Rio Grande do Sul. After 2004, Acre and southern Amazonas exhibited high rates that spread to northern Rondônia from 2016 to 2020. The Joinpoint model indicated an increasing trend in hepatitis C mortality in Brazil from 2000 to 2015, followed by a decreasing trend and a 25% reduction in Brazilian hepatitis C mortality after 2015, with greater reductions in the southern region and less in the northeastern region. In Ceará, hepatitis C mortality was lower than in the rest of the country; however, it is on an upward curve. Phase two consisted of analyzing treatment effectiveness. Between October 2015 and December 2023, 1,743 patients were treated with DAAs in Ceará, with 1,588 included in this study. Only 26.3% of treated patients in Ceará were from the interior of the state. Of the 1,588 patients, 513 were excluded from the analysis due to a lack of information, resulting in a final sample of 1,075 patients. The effectiveness of treatments for hepatitis C in Ceará was 96.4%, similar among HIV carriers, liver and kidney transplant recipients, and co-infected patients (HCV/hepatitis B). SVR was significantly lower in cirrhotic patients, especially in decompensated patients (Child C). Nine deaths were documented during treatment, with seven cirrhotic patients and two liver transplant recipients. Severe adverse events were significantly associated with ribavirin use. The indication for liver transplantation due to hepatitis C significantly decreased in Ceará after the introduction of DAAs. Conclusions: Hepatitis C mortality in Brazil has decreased heterogeneously after the introduction of DAAs in 2015. In Ceará, hepatitis C mortality continues to rise. Treatment with DAAs has proven to be effective and safe. The addition of ribavirin did not increase SVR and elevated severe adverse events. The small proportion of treated patients from the interior indicates the need for decentralization of specialized care for the elimination of hepatitis C in Ceará.